Oxygen Vacancy‐Mediated Growth of Amorphous Discharge Products toward an Ultrawide Band Light‐Assisted Li–O2 Batteries - Li, Fei; Li, Ma‐Lin; Wang, Huan‐Feng; Wang, Xiao‐Xue; Zheng, Li‐Jun; Guan, De‐Hui; Chang, Li‐Min; Xu, Ji‐Jing; Wang, Yu (Advanced materials (Weinheim), 2022)
Photoassisted electrochemical reaction is regarded as an effective approach to reduce the overpotential of lithium–oxygen (Li–O2) batteries. However, the achievement of both broadband absorption and long term battery cycling stability are still a formidable challenge. Herein, an oxygen vacancy‐mediated fast kinetics for a photoassisted Li–O2 system is developed with a silver/bismuth molybdate (Ag/Bi2MoO6) hybrid cathode. The cathode can offer both double advantages for light absorption covering UV to visible region and excellent electrochemical activity for O2. Upon discharging, the photoexcited electrons from Ag nanoplate based on the localized surface plasmon resonance (LSPR) are injected into the oxygen vacancy in Bi2MoO6. The fast oxygen reaction kinetics generate the amorphous Li2O2, and the discharge plateau is improved to 3.05 V. Upon charging, the photoexcited holes are capable to decompose amorphous Li2O2 promptly, yielding a very low charge plateau of 3.25 V. A first cycle round‐trip efficiency is 93.8% and retention of 70% over 500 h, which is the longest cycle life ever reported in photoassisted Li–O2 batteries. This work offers a general and reliable strategy for boosting the electrochemical kinetics by tailoring the crystalline of Li2O2 with wide‐band light. A facile oxygen vacancy‐mediated fast kinetics for an ultrawide band photoassisted Li–O2 system is developed. The bifunctional Ag/Bi2MoO6 cathode is favorable to promoting the oxygen reduction reaction and oxygen evolution reaction kinetics due to the discharge products is amorphous Li2O2. The reaction mechanism is revealed by in situ X‐ray diffraction and Raman spectroscopy.